Rapid mixing using two-phase hydraulic focusing in microchannels - Wu, Zhigang (2012)
Rapid mixing is important in biomedical analysis. In this study, rapid mixing is obtained through two-phase hydraulic focusing in microchannels. Two mixing streams are focused by two sheath streams. Assuming a laminar flow in the channel, the spreading behavior of the two immiscible fluids is modeled and solved analytically. The results show that both viscosity ratio and flow rate ratio between the sheath flow and the sample flow can affect the focusing ratio. Thus, the mixing path of the sample flows can be adjusted by either viscosity ratio or flow rate ratio. Furthermore, an analytical model was proposed and solved for convective/diffusive mixing between the sample streams. According to this model, the focusing ratio is a key parameter for rapid mixing. A fully polymeric micro mixer was fabricated and tested for verification of the presented analytical models. The micromixer was fabricated by laser micromachining and adhesive bonding. The characterization results show the promising potential of mixing in microscale using two-phase hydraulic focusing.